Elevating Student Voice and Levelling Traditional Power Hierarchies Through Open Textbook Co-Creation: What Do Students Say? - Bianca Masuku; Glenda Cox; Michelle Willmers (Social Sciences)
There are calls for the democratisation of higher education in line with the principles of social justice. Collaboration with students offers the potential for creating a more inclusive higher education environment, and open textbook development initiatives can be a vehicle for change. This paper focuses on the experiences of students as co-creators in open textbook initiatives at the University of Cape Town, South Africa. Drawing on interviews with 11 open textbook collaborators, this paper utilises Nancy Fraser’s social justice framework to explore students’ perspectives on injustices, challenges of collaboration and co-creation, and power dynamics in student–staff partnerships. The study shows that students experience and navigate various injustices in their classroom contexts related to economic maldistribution, cultural misrecognition and political misrepresentation. It reveals a complex interrelationship between student voice, power dynamics in the classroom, and the power of student–staff partnerships to build confidence and flatten hierarchies in open textbook co-creation. The student views presented here provide powerful evidence of a range of benefits they experience when the traditional hierarchies between student and lecturer are levelled through collaborative open textbook development processes. Results indicate that co-creation activities enabled them to have a voice through the power of publication and own their academic journeys.